Autoimmune thyroid disease in euthyroid subjects (2018)
OBJECTIVE: To determine the prevalence of thyroid autoantibodies and the associated factors in euthyroid subjects. METHODS: In this study, 300 euthyroid subjects chosen by stratified sampling from an inception cohort of 1335 individuals were included. None of the subjects was under treatment. Thyroid function was evaluated by measuring serum levels of TSH (0.3-4.5 μIU / ml) and FT4 (5.2-12.7μg / dl). In addition, anti-peroxidase (TPOAbs), anti-thyroglobulin (TgAbs), and anti-TSH receptor (TrAbs) autoantibodies were evaluated together with other 23 autoantibodies and vitamin D levels. The analysis included sociodemographic, clinical, and environmental characteristics. Data were analyzed by chi-square (χ2), Kruskal-Wallis, Mann-Whitney and logistical regression tests. RESULTS: Thyroid autoimmunity was observed in 15.3% of the subjects (TPOAbs in 11.3% and TgAbs in 2%). In six individuals, both autoantibodies were positive. TrAbs were not detected in any individual. Familial thyroid disease (P = 0.021,  = 3.4 CI: 1.2 – 9.5), low libido (P = 0.013,  = 3.8 CI: 1.3 – 10.6), the presence of other ADs (P = 0.014,  = 10.8 CI: 1.6 – 72.9) were associated with thyroid autoantibodies. In addition, VitD insufficiency (P= 0.03), never smoke (P = 0.010,  = 6.9 CI: 1.6 – 30.4), drinking more than 4 cups of coffee (P = 0.036,  = 3.8 CI: 1.1 – 13.1), and higher number of years exposed to wood smoke (P = 0.04), were associated with thyroid autoantibodies. Similar the last analysis, the presence of TPOAbs was associated with familial thyroid disease (P = 0.003,  = 4.9 CI: 1.7 - 14.0), never smoke (P = 0.002,  = 5.7 CI: 1.4 - 21.0), drinking > 4 cups of coffee (P = 0.047,  = 3.6 CI: 1.1 - 13.1), low libido (P = 0.001,  = 5.7 CI: 2.0 - 16.3). In addition, the presence of SS-A / Ro52 (P = 0.009,  = 36.7 CI: 2.5 - 549.9), and Ku (P = 0.046,  = 10.2 CI: 1.1 - 100.7), also was related to these autoantibodies. Regarding TgAbs, the presence of African ancestry (P = 0.01,  = 10.5 CI: 1.7 – 63.2), SS-A / Ro52 (P = 0.03,  = 15.8 CI: 1.2 – 198.6), and CENP-B (P = 0.02,  = 31.2 CI: 1.8 – 565.9) was associated with TgAbs. CONCLUSIONS: Subclinical thyroid autoimmunity is not rare. Environmental, genetic, and immunological factors as well as ancestry are associated risk factors. These results will facilitate the implementation of screening strategies in order to provide timely diagnosis and treatment.